New chances given to historic buildings by implementing revitalisation projects and adapting the premises to serve new functions - Wrana, Jan; Jarocka-Mikrut, Aleksandra (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
The article concerns the issue of revitalizing historical buildings by assigning new functions to them. The authors of the writing provide examples of constantly dilapidating edifices in Lublin and their brief historical outlines. Basing on the expert’s report concerning Sobiescy Palace in Lublin, the writers present problems resulting from the technical condition of this as well as other historical buildings. Chances for improving the conditions of such properties by including them in a completely new functional programme are seen by authors. In order to support this thesis, the writers present already implemented revitalization projects in Poland by assigning various new ones, e.g. living and public utility functions to the buildings.